Analysis of the Implementation of the Merdeka Curriculum in Social Studies Subjects in Elementary Schools - Ewa Ardiansyah; Ratnah Ratnah (Council: Education Journal of Social Studies, 2024)
The objectives of this study are: 1) to determine the role of teachers in teaching Social Studies using the Merdeka curriculum; 2) to identify the challenges faced by teachers in teaching Social Studies using the Merdeka curriculum. This research employs a descriptive qualitative method, where the data consists of observations and direct interviews with field experts. Data collection techniques include interviews, observations, and documentation. The sample selection for the study is purposively determined based on the expertise of the informants in providing necessary information to the researcher. Data analysis involves three steps: data reduction/selection, data interpretation, and conclusion drawing. Based on the research findings: 1) Teachers in Grade IV actively employ a scientific approach, encouraging students to be actively engaged in learning through various methods and models; 2) Challenges faced by teachers in implementing the Merdeka curriculum include excessive assessment criteria for students and inadequate teaching support facilities provided by the school, which hinder the effective implementation of the Merdeka curriculum